2016
DOI: 10.1099/ijsem.0.001041
|View full text |Cite
|
Sign up to set email alerts
|

Halanaeroarchaeum sulfurireducens gen. nov., sp. nov., the first obligately anaerobic sulfur-respiring haloarchaeon, isolated from a hypersaline lake

Abstract: Halanaeroarchaeum sulfurireducens gen. nov., sp. nov., the first obligately anaerobic sulfur-respiring haloarchaeon, isolated from a hypersaline lake

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…strain DL1 is an Antarctic strain that is characterized by a preference for catabolism of amino acids (especially branched chain amino acids), and does not utilize glycerol (Williams et al ., ), and Haa. sulfurireducens is a close relative of Halobacterium but has a very limited carbon metabolism (Sorokin et al ., ). The GlpA2 protein from Halobacterium sp.…”
Section: G3pdh (Ec 1153)mentioning
confidence: 97%
See 1 more Smart Citation
“…strain DL1 is an Antarctic strain that is characterized by a preference for catabolism of amino acids (especially branched chain amino acids), and does not utilize glycerol (Williams et al ., ), and Haa. sulfurireducens is a close relative of Halobacterium but has a very limited carbon metabolism (Sorokin et al ., ). The GlpA2 protein from Halobacterium sp.…”
Section: G3pdh (Ec 1153)mentioning
confidence: 97%
“…Haa. sulfurireducens is an obligate anaerobe found in anoxic environments (e.g., deep‐sea salt‐saturated anoxic Lake Medee; anoxic sediments and brines from hypersaline lakes in Kulunda Steppe, Russia) and is limited to growth using acetate and pyruvate as carbon sources, and elemental sulfur as the electron acceptor (Messina et al ., ; Sorokin et al ., ). In soda lakes, instead of Dunaliella (Falb et al ., ), haloalkaliphilic cyanobacteria are the major primary producers (Sorokin et al ., ) and they synthesize glycine betaine, sucrose, trehalose, and glucosylglycerol as compatible solutes rather than glycerol (Klähn and Hagemann, ).…”
Section: Concluding Remarks: Gene Repertoire and Haloarchaeal Ecophysmentioning
confidence: 97%
“…This has changed with the latest discovery of a strictly anaerobic acetate-oxidizing and S 0 -reducing haloarchaeon Halanaeroarchaeum sulfurireducens (HAA; Sorokin et al , 2016a). The in-depth characterisation of cultivated representatives demonstrated that aerobic respiration is not any longer a universal feature in the haloarchaea (Messina et al , 2016; Sorokin et al , 2016a,b). Moreover, this previously overlooked metabolic type underscores the ongoing metabolic diversification within haloarchaea (Sousa et al , 2016) and strengthens the evidence for involvement of this euryarchaeal branch in biogeochemical sulfur cycling linked to terminal anaerobic carbon mineralisation in hypersaline anoxic habitats.…”
Section: Introductionmentioning
confidence: 99%
“…To date, five bacterial and two archaeal strains have been isolated and described (2). Publicly available genome sequences exist for only Halarsenatibacter silvermanii SLAS-1 T (3, 4) and two strains of Halanaeroarchaeum sulfurireducens (5, 6). …”
Section: Genome Announcementmentioning
confidence: 99%